1999
DOI: 10.3141/1684-08
|View full text |Cite
|
Sign up to set email alerts
|

Westergaard Curling Solution Reconsidered

Abstract: An in-depth and systematic examination is presented of the effect of temperature gradients on slab-on-grade pavements. The main objective for the examination was the development of practical design tools for use in a typical engineering office. This has been achieved by a critical reconsideration of the literature, a synthesis of currently available analytical resources, and the implementation of recent technological achievements promulgated in related areas of engineering. Prominent among these are the applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 3 publications
4
12
1
1
Order By: Relevance
“…Despite this argument, Ioannides et al (1985) later has indicated that the ILLI-SLAB finite element results closely fall between those predicted by Westergaard and Bradbury. The ILLI-SLAB stresses are the minor principal (tensile) stresses occurring at the top fiber of the slab corner.…”
Section: Corner Loadingsupporting
confidence: 43%
“…Despite this argument, Ioannides et al (1985) later has indicated that the ILLI-SLAB finite element results closely fall between those predicted by Westergaard and Bradbury. The ILLI-SLAB stresses are the minor principal (tensile) stresses occurring at the top fiber of the slab corner.…”
Section: Corner Loadingsupporting
confidence: 43%
“…In the dimensioning of models the following has been considered: that the distance from the center of load application, the center of the tire forklift track, to the nearest edge of the slab must be greater than 1.75*L (Ioannides et al, 1985), where L is the relative stiffness (Eq [1]).…”
Section: Application Of the Fem For Sizing Concrete Slabs For Forkliftsmentioning
confidence: 99%
“…The reference point shown in the figure is located at the mid-slab 300 mm away from the edge. Since tire pressure, tire contact area, and tire aspect ratio have an impact on the mechanistic responses of rigid pavements obtained from the finite element method (Ioannides et al 1985), wheel load may not be treated as a discrete point load. Thus, in the formation of influence surfaces, it is of importance to appropriately select contact pressure, contact area, and aspect ratio for the unit load.…”
Section: Experimental Matrixmentioning
confidence: 99%